Impact of sharecropping on rice productivity in some areas of Khulna district - Ahmed, MF; Billah, MM (Bangladesh Journal of Agricultural Research, 2018)
The study reveals the effect of sharecropping on rice productivity in some selected areas of Khulna District in the South-West region of Bangladesh. Access to land for the landless farmer is governed by informal land tenure arrangement, which in turn affects the productivity of the rice farm. In exploring the debate on sharecropping and farm efficiency, the present study has been conducted to assess the effect of sharecropping on rice productivity. During June 2014, a field survey was conducted by using a semi-structured questionnaire in two villages of Khulna District where sharecropping is one of the dominant land tenure arrangements in rice farming. A Cobb-Douglas production function estimation showed that type of land ownership, use of fertilizers, human labor, and modern variety (MV) including hybrid seed and high yielding varieties (HYVs) of seed had the positive and significant influence on rice production. There was a significant mean difference between the sharecroppers and the owner farmers regarding their volume of rice production. The production volume of the owner farmers was significantly higher by around 781 kg ha-1. The study result from the production function revealed that on an average owner farmers’ output was significantly higher by 10% than that of the sharecroppers. The study also observed that higher land rent in form of a fixed amount of cash or a higher crop share demotivated the sharecroppers to supply the optimum level of input and to use the land intensively. The result implied that the sharecroppers are inefficient compared to the landowners. Therefore, it is recommended that sharing an equitable production cost and a justifiable crop sharing structure might be the better options to motivate the sharecropper to become more efficient concerning their volume of production. Bangladesh J. Agril. Res. 43(3): 417-430, September 2018